SKAP2 acts downstream of CD11b/CD18 and regulates neutrophil effector function - Bouti, Panagiota; Klein, Bart J. A. M.; Verkuijlen, Paul J. H.; Schornagel, Karin; van Alphen, Floris P. J.; Taris, Kees-Karel H.; van den Biggelaar, Maartje; Hoogendijk, Arie J.; van Bruggen, Robin; Kuijpers, Taco W.; Matlung, Hanke L. (Frontiers in Immunology, 2024)
The importance of CD11b/CD18 expression in neutrophil effector functions is well known. Beyond KINDLIN3 and TALIN1, which are involved in the induction of the high-affinity binding CD11b/CD18 conformation, the signaling pathways that orchestrate this response remain incompletely understood. Method: We performed an unbiased screening method for protein selection by biotin identification (BioID) and investigated the KINDLIN3 interactome. We used liquid chromatography with tandem mass spectrometry as a powerful analytical tool. Generation of NB4 CD18, KINDLIN3 or SKAP2 knock out neutrophils was achieved using CRISPR-Cas9 technology and the cells were examined for their effector function using flow cytometry, live cell imaging, microscopy, adhesion or antibodydependent cellular cytotoxicity (ADCC). Results: Among the 325 proteins significantly enriched, we identified Src Kinase-Associated Phosphoprotein2 (SKAP2), a protein involved in actin polymerization and integrin-mediated outsidein signaling. CD18 immunoprecipitation in primary or NB4 neutrophils demonstrated the presence of SKAP2 in the CD11b/CD18 complex at steady state. Under this condition, adhesion to plastic, ICAM-1 or fibronectin was observed in the absence of SKAP2, which could be abrogated by blocking the actin-rearrangements with latrunculin B. Upon stimulation of SKAP2-deficient neutrophils, adhesion to fibronectin was enhanced whereas CD18 clustering was strongly reduced. This response corresponded with significantly impaired CD11b/CD18-dependent NADPH oxidase activity, phagocytosis and cytotoxicity against tumor cells. Conclusion: Our results suggest that SKAP2 has a dual role. It may restrict CD11b/CD18-mediated adhesion only under resting conditions, but its major contribution lies in the regulation of dynamic CD11b/CD18-mediated actin-rearrangements and clustering as required for cellular effector functions of human neutrophils.